LincRNA Plays a Role in the Effect of CYP46A1 Polymorphism in Alzheimer’s Disease – Related Pathology - Chen, Yang; Li, Hui-Yun; Zeng, Fan; Chen, Le; Zhou, Fa-Ying; Peng, Ze-Yan; Yang, Hai; Zhou, Hua-Dong; Wang, Yan-Jiang; Li, Ling (Frontiers in Aging Neuroscience, 2020)
Polymorphism of the cholesterol-24S-hydroxylase (CYP46A1) gene is thought to be a risk factor for Alzheimer’s disease (AD). A single nucleotide polymorphism (T/C) in intron 2, rs754203, has been confirmed to be implicated in AD. Rs754203 is also located in the long intronic non-coding RNA (LincRNA) sequence. Meanwhile, the LincRNA has already been shown to be involved in the pathology of many diseases. Thus, the present study aimed to investigate the role of LincRNA in the CYP46A1 gene expression and related AD pathology. SH-SY5Y cells with overexpressed TT or CC genotype CYP46A1 were used. Through RT-PCR, Western blot and ELISA assays, we found that LincRNA can affect the CYP46A1 gene expression and the production of 24-OHC and Aβ. Overexpression of LincRNA can significantly inhibit CYP46A1 expression and 24-OHC production, as well as increasing the Aβ expression level. Silencing of LincRNA confirmed the role that it plays in the regulation of CYP46A1, as well as the production of 24-OHC and Aβ. In addition, this effect was stronger in the A type LincRNA than in the G type LincRNA. Results from dual luciferase assays show that LincRNA inhibited the activity of the CYP46A1 gene promoter. This study indicated a possible new role of LincRNA and provided a new way to look into the relationship between CYP46A1 polymorphism and AD pathology. This may point a novel pathway to explore AD therapy.